Performance comparison of flux schemes for numerical simulation of high-speed inviscid flows. (1st January 2014) - John, Bibin; Sarath, G.; Kulkarni, Vinayak; Natarajan, Ganesh
Numerical investigations to assess the performance of different flux schemes for the spatial discretisation of the Euler equations have been performed. The schemes employed in the study include flux vector and flux difference splitting schemes as well as hybrid schemes. The schemes are cast in an unstructured high-order finite volume framework and are studied on typical engineering problems in the supersonic and hypersonic regimes. While all the flux schemes perform well in the supersonic and low hypersonic range, their performance show a marked change in the high Mach number regimes. Numerical experiments suggest that the AUSM family of schemes is the most accurate while the Rusanov scheme is the most robust for the range of Mach numbers considered in the study. These studies indicate that a robust and accurate numerical solver for high-speed compressible flows necessitate the use of blended schemes that provide a right balance between accuracy and numerical dissipation.